Cell Mysteries and the Paradigm of Sexual Reproduction - Paunesku, Tatjana (Zygon, 2025)
Biological evolution is an indisputable reality of life, regardless of our ability to conceptualize it. Life of a species cannot exist without death of individuals and birth of new ones. As long as this cycle exists, biological evolution is inevitable, with new speciation as its eventual outcome. The theory of evolution was formulated by Charles Darwin, but understanding of what life is and how it functions owes equally as much to Matthias Jakob Schleiden’s and Theodore Schwann’s cell theory. These three naturalists from the nineteenth century gave us the basis for biology as it is today, and yet cells and evolution are still only partially understood. Life remains mysterious. Death remains a focus of most world religions. This article gives a tremendously abbreviated current understanding of the history of life until this moment in an effort to motivate us to think about life on Earth as it really is—with all extant and lost living beings of Earth related through a common ancestor and made of water and dust.